Development of a molecularly imprinted polymer for uric acid sensing based on a conductive azopolymer: Unusual approaches using electrochemical impedance/capacitance spectroscopy without a soluble redox probe - Trevizan, Heitor Furlan [UNESP]; Olean-Oliveira, André [UNESP]; Cardoso, Celso Xavier [UNESP]; Teixeira, Marcos F.S. [UNESP] (Elsevier, 2021)
In the present study, we report the use of an electrochemical sensor for uric acid using a molecularly imprinted polymer (MIP) as a molecular recognition platform. The MIP was based on an azopolymer electropolymerized in the presence of uric acid used as a template molecule. The azo group of the polymer contributes to the quantifiable redox capacitance of the electrode surface, which can be probed by impedance/capacitance spectroscopy. Thus, the advantage of the developed sensor is its ability to perform direct measurements without a soluble redox probe. The molecularly imprinted polymer can sensitively transduce the recognition and binding of specific analytes by redox capacitance. Through electrochemical impedance spectroscopy (EIS) and electrochemical capacitive spectroscopy (ECS), unusual approaches were able to obtain different analytical curves with distinct characteristics, reaching a limit of detection of 0.160 μmol L−1.
Keywords: Azopolymer; Molecular recognition; Molecularly imprinted polymer; Resistive/capacitive sensor; Uric acid; Without redox probe